Phytochemical Screening and Antimicrobial Activities of Methanolic and Aqueous Leaf Extracts of Carica papaya Grown in Rwanda - Cyuzuzo Callixte; Nsanzimana Jean Baptiste; Heny Arwati (Molecular and Cellular Biomedical Sciences, 2020)
Background: Nowadays, microbial infections remain as the leading cause of infectious diseases and human death worldwide. The use of plant-derived medicines is currently increasing in the treatment of various diseases. Papaya leaves have proteolytic enzymes and phytoconstituents with antimicrobial properties. Rwandan citizens use papaya leaves to treat hair dandruff, wounds and burns.Materials and Methods: Papaya leaves were collected and allowed to dry under the shed at room temperature for 14 days. The powdered plant materials were soaked separately in clean flask and extracted successively using maceration method with water and methanol. Qualitative phytochemical screening was conducted by using specific standard procedures. Antimicrobial activity assays of all the extracts were performed by agar well diffusion method and determined by measuring the zones of inhibition with transparent scale.Results: Phytochemical screening revealed the presence of alkaloids, carbohydrates, tannins, flavonoids, steroids and phenolic compounds. In this observation, all the extracts exhibit significant inhibitory activity against all test pathogens ranging from 2 mm to 26 mm of diameter. Methanol extracts showed the maximum activity against Candida albicans (inhibition zone: 26±0.11 and activity index: 1.23). Minimum inhibition concentration values ranges between 3.175 mg/mL and 12.5 mg/mL.Conclusion: The results indicate that Carica papaya leaves could be very potent source of antimicrobial agents and secondary metabolites that can be used by pharmaceutical industries to produce medicines.Keywords: Carica papaya, antimicrobial, agar well diffusion, phytochemical screening, zone of inhibition, activity index